2009
DOI: 10.1080/07853890802609542
|View full text |Cite
|
Sign up to set email alerts
|

Substantial variation in the cardiac differentiation of human embryonic stem cell lines derived and propagated under the same conditions—a comparison of multiple cell lines

Abstract: The hESC lines derived in the same laboratory varied considerably in their potential to differentiate into beating cardiomyocytes. None of the expression markers could clearly predict cardiac differentiation potential, although the expression of early cardiomyogenic genes was upregulated in the best cardiac line. The proper cardiomyocyte characteristics and pharmacological response indicate that these cells could be used as a model for human cardiomyocytes in pharmacological and toxicological analyses when inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 38 publications
5
64
0
Order By: Relevance
“…A high phenotypic variability has been observed among different lines described as ‘healthy controls’ (sometimes age and gender matched) and used as a reference in multiple studies (Figure 3). In a study on four isogenic lines from healthy donors (Kyttälä et al , 2016), up to 158 genes were found to be differently expressed among the lines; some were imprinted, evidence for a role of epigenetic memory in determining the phenotype and differentiation potential of hPSC, possibly by affecting their response to growth factors (Pekkanen‐Mattila et al , 2009). A consequence may then include differential responses to drugs.…”
Section: Limitations In Applicability Of Hipsc‐cm To Large‐scale Drugmentioning
confidence: 99%
“…A high phenotypic variability has been observed among different lines described as ‘healthy controls’ (sometimes age and gender matched) and used as a reference in multiple studies (Figure 3). In a study on four isogenic lines from healthy donors (Kyttälä et al , 2016), up to 158 genes were found to be differently expressed among the lines; some were imprinted, evidence for a role of epigenetic memory in determining the phenotype and differentiation potential of hPSC, possibly by affecting their response to growth factors (Pekkanen‐Mattila et al , 2009). A consequence may then include differential responses to drugs.…”
Section: Limitations In Applicability Of Hipsc‐cm To Large‐scale Drugmentioning
confidence: 99%
“…In the vicinity of the sarcomeres, mitochondia are also present. In addition, cells have intercalacted disks with gap junctions and desmosomes (Kehat, Kenyagin-Karsenti et al 2001;Snir, Kehat et al 2003;Pekkanen-Mattila, Kerkela et al 2009). …”
Section: Structural Analysismentioning
confidence: 99%
“…Another approach to estimate the cardiac differentiation efficiency and follow the differentiation is to quantify the mRNA levels of cardiac markers and cardiac differentiation markers. hESC-CM differentiation can be predicted by the transient expression of the early mesodermal marker Brachyury T. Brachyury T expression peak is detected at day 3 in END-2 co-cultures (Beqqali, Kloots et al 2006;Pekkanen-Mattila, Kerkela et al 2009) and a day later in EBs (Bettiol, Sartiani et al 2007;Pekkanen-Mattila, Pelto-Huikko et al 2010). Brachyury T belongs to the family of transcription factors which are encoded by the T-box genes (Showell, Binder et al 2004).…”
Section: Estimation Of Differentiation Efficiency and Expression Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, monitoring expression of AFP alone is not suffi cient to conclude a hepatic phenotype. Moreover, genetic variation between hESC lines is known to infl uence the differentiation properties, and additional studies employing more than one hESC line are needed [16][17][18].…”
Section: Differentiation Of Hesc Using the I-protocolmentioning
confidence: 99%